2022
DOI: 10.1111/1471-0528.17093
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and maternal outcomes after maternal biologic use during conception and pregnancy: A systematic review and meta‐analysis

Abstract: Background: Biologic medications, specifically tumour necrosis factor-α (TNF-α) inhibitors, have become increasingly prevalent in the treatment of chronic inflammatory disease (CID) in pregnancy.Objective: To determine pregnancy outcomes in women with CID exposed to biologics during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…Its unique structure may prevent fetal exposure to the drug during pregnancy ( 31 , 32 ). Both of them can be safely used in pregnancy to treat some autoimmune diseases and have recently been introduced to clinical trials on refractory recurrent spontaneous miscarriages ( 23 , 29 , 33 ). Despite little experience in applying CZP for pregnancy rescue therapy, we will further consider its use because its unique structure could avoid placental transfer, making it a better, safer choice in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Its unique structure may prevent fetal exposure to the drug during pregnancy ( 31 , 32 ). Both of them can be safely used in pregnancy to treat some autoimmune diseases and have recently been introduced to clinical trials on refractory recurrent spontaneous miscarriages ( 23 , 29 , 33 ). Despite little experience in applying CZP for pregnancy rescue therapy, we will further consider its use because its unique structure could avoid placental transfer, making it a better, safer choice in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…45 Finally, regarding the use of biologics in pregnancy, the evidence demonstrates no difference in pregnancy outcome, including that of fetal structural differences, in those on biologic treatment, suggesting these as a safe third-line alternative in the management of disease remission in pregnancy. 50 Anti-TNF agents including adalimumab or infliximab are commonly used in the management of sarcoidosis. Their use is nuanced by concern around neonatal immunological effects, particularly the risk of immunosuppression with avoidance of live vaccines in early life.…”
Section: Management Of Sarcoidosis In Pregnancymentioning
confidence: 99%
“…Several systematic literature reviews and meta-analyses have been conducted examining exposure to biologics and pregnancy outcomes. 2,10,12 Most of these studies have concluded that prenatal exposure to biologics was not associated with either elevated or reduced risks of adverse pregnancy outcomes after controlling for disease and underlying clinical characteristics (i.e., comparing those exposed to disease-matched controls). However, comparing pregnant users to pregnant nonusers or discontinuers in an observational study design is challenging, due to confounding by disease severity.…”
Section: Potential Benefitsmentioning
confidence: 99%
“…For maternal serious infection, there is evidence of an increased risk of serious infection in pregnancy associated with biologic use. 12,17 Regarding the postpartum period specifically, a Canadian study found that the occurrence of serious postpartum infection was low and did not show any association with biologic exposure during pregnancy. 23 When assessing risk of infant infection after in utero exposure to biologics, one meta-analysis reported an increased risk of infections in newborns born to pregnant people with immune-mediated inflammatory disease exposed to TNF inhibitors compared with untreated, disease-matched controls.…”
Section: Potential Benefitsmentioning
confidence: 99%